2012
DOI: 10.22599/bioj.71
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, referral and attendance: results from an inner city school based vision screening programme

Abstract: Aim: To review the children's school vision screening service in order to investigate the uptake, referral pattern and follow-up attendance. Methods: The children were screened in school. The vision screening results of the children screened in the academic year 2011-2012 were reviewed for both uptake of screening and subsequent attendance for the follow-up assessment. Attendance outcomes from children referred to an optometrist of their choice and also those children referred to the Hospital Eye Service (HES)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…It has been shown that children from socioeconomically deprived households have an increased prevalence of vision problems, 31 32 which may in part be due to inequality in accessing health services. 33 The Bradford vision screening programme covers 97% of children 14 and therefore does not exclude children from the lower socioeconomic areas. The high levels of deprivation in the city may help explain the higher prevalence level of poor VA. Educational attainment is multifactorial and influenced by social disadvantage and demographic factors, differences manifest early and are demonstrable through gaps in literacy achievement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that children from socioeconomically deprived households have an increased prevalence of vision problems, 31 32 which may in part be due to inequality in accessing health services. 33 The Bradford vision screening programme covers 97% of children 14 and therefore does not exclude children from the lower socioeconomic areas. The high levels of deprivation in the city may help explain the higher prevalence level of poor VA. Educational attainment is multifactorial and influenced by social disadvantage and demographic factors, differences manifest early and are demonstrable through gaps in literacy achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the nature of the programme being conducted after school entry, coverage is high at 97%. 14 In total, 11 186 children from 123 primary schools across the city participated in the vision screening programme. In total, 5836 BiB children were eligible for the study (started school between September 2012 and July 2014) and 4953 (85%) BiB children had completed the vision screening programme prior to the data linkage ( figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…2 Early detection programmes can only be effective if those identified with poor vision are appropriately treated. In deprived communities both locally 3 and internationally 4 attendance rates following vision screening are reported between 30% to 40%. 3 In addition, studies have shown poor adherence to spectacle wear 5–7 ; therefore, a high proportion of children with identified needs do not access ophthalmic services and subsequent treatment.…”
Section: Introductionmentioning
confidence: 99%
“…21 The length of time that patients were under the care of the HES was also significantly lower for school screening compared with pre-school screening (9.01 months versus 25.24 months). Children under review for vision treatment are typically followed up every 6-12 weeks.…”
Section: Discussionmentioning
confidence: 93%